Assessment of serum cytokines predicts clinical and endoscopic outcomes to vedolizumab in ulcerative colitis patients. Issue 7 (18th February 2020) - Bertani, Lorenzo; Baglietto, Laura; Antonioli, Luca; Fornai, Matteo; Tapete, Gherardo; Albano, Eleonora; Ceccarelli, Linda; Mumolo, Maria Gloria; Pellegrini, Carolina; Lucenteforte, Ersilia; de Bortoli, Nicola; Bellini, Massimo; et al.
Abstract : Aims: Vedolizumab (VDZ) prevents migration of activated leucocytes into inflamed mucosa. This study aimed to assess the patterns of serum cytokines in ulcerative colitis (UC) patients at baseline and during VDZ treatment, and to investigate their association with mucosal healing and clinical remission. Methods: We enrolled consecutive UC patients eligible for treatment with VDZ. A panel of serum cytokines were measured by fluorescence assay at weeks 0, 6 and 22. Colonoscopy was performed at baseline and week 54, to evaluate mucosal healing. The time trends of serum cytokines were analysed by log‐linear mixed effect models, and their prognostic accuracy was evaluated by logistic regression. Results: Out of 27 patients included in the analysis, at week 54 mucosal healing was achieved in 12 (44%) and clinical remission in 17 (63%). Mucosal healing was associated with higher interleukin (IL)‐8 values at baseline and with significant decrease in IL‐6 and IL‐8 levels over the first 6 weeks. A significant reduction of IL‐6 and IL‐8 levels over the first 6 weeks of treatment was associated also with clinical remission. Logistic models including, among the predictors, IL‐6 and IL‐8 at baseline and their changes over the first 6 weeks of treatment had 83% sensitivity and 87% specificity to predict mucosal healing, and 82% sensitivity and 90% specificity to predict clinical remission. Conclusion: In UC patients, the serum patterns of IL‐6 and IL‐8 at baseline and over the first 6 weeks of treatment with VDZ could be useful to predict therapeutic outcome.